Mechanisms underlying cardiac vulnerability to electric shocks within the three-dimensional volume of the rabbit ventricles - Maharaj, T; Rodriguez, B; Blake, R; Trayanova, N; Gavaghan, D (2006)
The goal of this study is to investigate the contribution of transmural heterogeneities in action potential duration (APD) to the mechanisms of cardiac vulnerability to electric shocks, in an attempt to better understand the mechanisms behind defibrillation failure. This study used a three-dimensional, geometrically accurate finite element bidomain model of the rabbit ventricles. Transmural heterogeneities in ionic currents were incorporated based on experimental data to generate the transmural APD profile recorded in adult rabbits during pacing. Results reveal that the upper limit of vulnerability (ULV) is 30.5V/cm and the vulnerable window (VW) extends from CI=120ms to CI=190ms. Examination of shock-end virtual electrode polarisation and postshock electrical activity reveals that increased dispersion in postshock repolarisation within the LV wall play a key role in the existence of the ULV whereas mechanisms underlying the existence of the VW are determined by shock-end refractoriness in the septum.